CRISPR/Cas9‐Based Genome Editing and its Applications for Functional Genomic Analyses in Plants. Issue 3 (11th January 2019) - Li, Jun; Li, Yan; Ma, Ligeng
Abstract: The ability to modify complex genomes precisely to create specific mutants is the holy grail of basic research and applied genetics in the postgenomic era. Programmable sequence‐specific nucleases (e.g., zinc finger nucleases, transcription activator‐like effector nucleases, and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated (Cas) systems (e.g., CRISPR/Cas9)), which induce targeted DNA breaks that are then repaired by endogenous repair machinery to generate mutants in a variety of organisms, are being developed at an unprecedented rate. Herein, this paper reviews the history, structure, and biological function of CRISPR/Cas systems, describing how it has been adapted for genome editing (especially CRISPR/Cas9, which has prompted a genome engineering revolution), and emphasizes recent applications and advances in the functional annotation of plant genomes and crop genetic improvement. In addition, the challenges of using the CRISPR/Cas9 system and strategies for improving its specificity are discussed. This review also introduces the creation of CRISPR‐edited DNA‐free plants, which may be more publicly acceptable than other genetically modified organisms. Finally, the future directions and applications of the CRISPR/Cas9 system are speculated on. Abstract : CRISPR/Cas9, adapted from prokaryotic adaptive immunity systems, induces targeted DNA double‐strand breakage, which triggers the endogenous DNA repair system. After the double‐strand break is repaired, various mutations (single gene knockout, multiplex gene knockouts, deletions, replacements, or insertions) are generated, which have great value and play an important role in the functional annotation of plant genomes and crop genetic improvement.